The character of pure spinors - Berkovits, N.; Nekrasov, N. (Springer, 2005)
The character of holomorphic functions on the space of pure spinors in 10, 11 and 12 dimensions is calculated. From this character formula, we derive in a manifestly covariant way various central charges which appear in the pure spinor formalism for the superstring. We also derive in a simple way the zero momentum cohomology of the pure spinor BRST operator for the D = 10 and D = 11 superparticle.
Keywords: covariant quantization of the superstring; pure spinors; fixed point formulae